2007
DOI: 10.1111/j.1745-4514.2007.00121.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF NaCl ON GELATION CHARACTERISTICS OF ACID- AND ALKALI-TREATED PACIFIC WHITING FISH PROTEIN ISOLATES

Abstract: The physicochemical properties of gels prepared from Pacific whiting protein isolated at pH 3 and 11 with three concentrations of NaCl were characterized after a pH readjustment to 7.0. The strongest gels were obtained from fish protein isolate (FPI) prepared at pH 11/150‐mM NaCl and conventional surimi. The protein solubilities of FPI treatments did not contribute significantly to their gel properties. Surface hydrophobicity and differential scanning calorimetry demonstrated that, in addition to adjusting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 79 publications
4
31
0
Order By: Relevance
“…However, when NaCl was added, the chloride ion preferentially binds with the positively charged amino acids to a stronger degree than the sodium ion. The system required more H + ion reach the approximately zero net charge needed to precipitate proteins (Thawornchinsombut & Park, 2007). Thus, the pI of myosin in 0.5 M NaCl was lower than pH 5.5.…”
Section: Dynamic Rheological Properties Of Fish Myosin Solutionmentioning
confidence: 99%
“…However, when NaCl was added, the chloride ion preferentially binds with the positively charged amino acids to a stronger degree than the sodium ion. The system required more H + ion reach the approximately zero net charge needed to precipitate proteins (Thawornchinsombut & Park, 2007). Thus, the pI of myosin in 0.5 M NaCl was lower than pH 5.5.…”
Section: Dynamic Rheological Properties Of Fish Myosin Solutionmentioning
confidence: 99%
“…Therefore, the SH groups available for disulfide formation and/or other interchanges were more limited during gelation of the acidtreated sample than of the alkali-treated sample. Thawornchinsombut and Park (2007) investigated the interactive effect of pH and ionic strength during protein solubilization on gelation properties of acid-and alkaliprocessed protein isolates from Pacific whiting. Results were compared to conventional surimi processing.…”
Section: Gel Qualitymentioning
confidence: 99%
“…Protein aggregation includes reversible (Arakawa, Bhat, & Timasheff, 1990) and irreversible aggregate formation (Kendrick et al, 1998). Protein gels in the presence of salt were shown to undergo heat-induced irreversible gelation (Thawornchinsombut & Park, 2007). Conversely, gels formed with native protein isolate without adding salt or other additives showed thermo-reversible properties (Brenner et al, 2009).…”
Section: Introductionmentioning
confidence: 96%
“…The process of heat-gelation involves an initial unfolding upon heating and subsequent aggregation of protein molecules. The heating usually has to be carried out at protein isoelectric point or at high ionic strength (Thawornchinsombut & Park, 2007), and often in the presence of different additives (Chen & Jaczynski, 2007). Various studies have reported the gelation of fish muscle protein without adding salt or other additives at neutral pH (Brenner, Nicolai, & Johannsson, 2009).…”
Section: Introductionmentioning
confidence: 99%